STUDENTS’ PERCEPTION OF LECTURER CODE-SWITCHING IN OFFLINE AND ONLINE ENGLISH CLASSES AT IAIN BONE SOUTH SULAWESI - Samsinar Samsinar; Sukardi Weda; Muhammad Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study employs a descriptive qualitative approach to explore students’ perceptions of lecturer code-switching in a hybrid English learning environment at IAIN Bone, South Sulawesi. The research site, IAIN Bone, is the largest higher education institution in Bone Regency, where hybrid learning known as combining online and offline instruction and it is still practiced there. This location was chosen based on initial observations showing that many students struggle to fully understand lessons delivered entirely in English. Participants in the study were fourth-semester students enrolled in an English Education hybrid class during the 2024/2025 academic year. Data were collected through semi-structured interviews and continued until data saturation was achieved. The findings indicate that code-switching positively influenced students’ learning experiences. Students reported that bilingualism in the context of code-switching helped them better understand the material, reduced their anxiety during lessons, and supported vocabulary development. They viewed the use of both Indonesian and English by lecturers not as a hindrance, but as a helpful instructional strategy. Overall, the students expressed favorable perceptions of code-switching, considering it an inclusive and effective approach in hybrid English language instruction. These insights suggest that code-switching can play a meaningful role in supporting student comprehension and engagement in bilingual learning environments.